The effect of socio-economic status, emotional intelligence and financial literacy as a mediation variable on personal financial management - Rahayu, Sri; Nuansari, Shindy Dwita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
This study aims to determine the effect of socioeconomic status and emotional intelligence with financial literacy as a mediating variable on the personal financial management of students at Alma Ata University, Yogyakarta. This research is a quantitative research with data collection techniques using a questionnaire. The research sample is 350 respondents. The sampling technique used was random sampling and was calculated using the Slovin formula. Primary data processing uses statistical product and service solutions (SPSS) analysis techniques and the methodologies used are path analysis, sobel test and robustness test. The results of this study state (1) there is a positive and significant influence of socioeconomic status, emotional intelligence and financial literacy on the personal financial management of Alma Ata University students; (2) there is a positive and significant influence of socio-economic status and emotional intelligence on the financial literacy of Alma Ata University students; (3) financial literacy is able to mediate socio-economic status and emotional intelligence on the personal financial management of Alma Ata University students; (4) there is no difference in the results of the analysis when the sample is broken down to carry out the robustness test, so the results of this research analysis are robust.